2019
DOI: 10.3171/2019.9.focus19660
|View full text |Cite|
|
Sign up to set email alerts
|

The T2-FLAIR–mismatch sign as an imaging biomarker for IDH and 1p/19q status in diffuse low-grade gliomas: a systematic review with a Bayesian approach to evaluation of diagnostic test performance

Abstract: OBJECTIVEWith the revised WHO 2016 classification of brain tumors, there has been increasing interest in imaging biomarkers to predict molecular status and improve the yield of genetic testing for diffuse low-grade gliomas (LGGs). The T2-FLAIR–mismatch sign has been suggested to be a highly specific radiographic marker of isocitrate dehydrogenase (IDH) gene mutation and 1p/19q codeletion status in diffuse LGGs. The presence of T2-FLAIR misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…On the other hand, the T2-FLAIR mismatch sign is an image-based molecular diagnostic marker that clinicians can readily incorporate into clinical practice, as both T2WI and FLAIR are routine MRI protocols for gliomas. The T2-FLAIR mismatch sign is an imaging surrogate specific for IDH mt, non-CODEL astrocytomas, performance of which several studies have validated ( 13 15 , 29 31 ). However, the sensitivity and NPV of the T2-FLAIR mismatch sign have been reported to be relatively low, as quite a few IDH mt, non-CODEL astrocytomas do not present the T2-FLAIR mismatch sign ( 13 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the T2-FLAIR mismatch sign is an image-based molecular diagnostic marker that clinicians can readily incorporate into clinical practice, as both T2WI and FLAIR are routine MRI protocols for gliomas. The T2-FLAIR mismatch sign is an imaging surrogate specific for IDH mt, non-CODEL astrocytomas, performance of which several studies have validated ( 13 15 , 29 31 ). However, the sensitivity and NPV of the T2-FLAIR mismatch sign have been reported to be relatively low, as quite a few IDH mt, non-CODEL astrocytomas do not present the T2-FLAIR mismatch sign ( 13 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the MRIbased T2-FLAIR mismatch sign was recognized as a visual-based imaging characteristic with good interobserver correlation that may determine the 1p/19q status in LGG. A recent systematic review suggested that the T2-FLAIR mismatch sign displayed a sensitivity and specificity of 30 and 73% in determining IDH mutated with 1p/19q co-deleted tumors, and 34 and 98% for IDH mutated with 1p/19q intact tumors (40). However, such imaging characteristics may be limited in clinical application due to the unbalanced sensitivity and specificity, and highthroughput quantitative features are intensively needed to better illustrate the radiological divergences and further predict the 1p/19q status non-invasively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Foltyn et al recognized the T2-FLAIR mismatch sign in 12 of 113 cases (10.6%) (Grade II and III gliomas) and in none of the 295 glioblastoma cases [19]. A recent meta-analysis by Goyal et al estimated the pooled accuracy of the T2-FLAIR mismatch sign in predicting IDH mutation based on data extracted from three studies focusing on the prediction of 1p/19q status in patients with LGG [11,14,15,24,25]. The pooled sensitivity and specificity rates were estimated to be as high as 31% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%